2021
DOI: 10.1016/j.pmedr.2021.101463
|View full text |Cite
|
Sign up to set email alerts
|

Association of childhood physical and sexual abuse with arthritis in adulthood: Findings from a population-based study

Abstract: Highlights Arthritis has been identified as one of the leading causes of disability in the United States. A little over one in four adults (27.6%) had arthritis. Respondents who experienced childhood physical abuse had 1.36 times higher risk of having arthritis. Respondents who experienced childhood sexual abuse had 1.36 times higher risk of having arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
0
3
0
6
Order By: Relevance
“…Our search identified 8320 articles, from which we included 85 studies reported in 87 articles ( Figure 1 ). 73 studies used a cross-sectional (Afifi et al, 2016 ; 2013 ; Alhalal et al, 2018 ; Anno et al, 2015 ; Badley et al, 2019 ; Baiden et al, 2021 ; Barron, 1997 ; Bendixen et al, 1994 ; Bottiroli et al, 2018 ; Brennenstuhl & Fuller-Thomson, 2015 ; Brown et al, 2018 ; Chartier et al, 2007 , 2010 ; Coles et al, 2015 ; Dennis et al, 2019 ; Díaz-Olavarrieta et al, 2002 ; England-Mason et al, 2018 ; Eriksen et al, 2016 ; Fowler et al, 2020 ; 2009 ; 2011 ; Hammond & Colman, 2020 ; Hanlon et al, 2020 ; Hart-Johnson & Green, 2012 ; Häuser et al, 2018 ; Jamieson & Steege, 1997 ; Jiao et al, 2015 ; Kamiya et al, 2016 ; Kascakova et al, 2020 ; Lee et al, 2009 ; Lin et al, 2021 ; Mays et al, 2021 ; McBeth et al, 2015 ; Nicol et al, 2016 ; Noteboom et al, 2021 ; Park et al, 2014a ; Pebole et al, 2022 ; Pierce et al, 2020 ; Reuchlein et al, 2016 ; Riedl et al, 2019 ; Sachs-Ericsson et al, 2007 ; 2017 ; Schrepf et al, 2018 ; Scott et al, 2011 ; Sheikh, 2018 , 2019 ; Shields et al, 2015 ; Sprang et al, 2020 ; Springer et al, 2007 ; Stickley et al, 2015 ; Talley et al, 1998 ; 1994 ; Tietjen et al, 2009 ; 2010 ...…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Our search identified 8320 articles, from which we included 85 studies reported in 87 articles ( Figure 1 ). 73 studies used a cross-sectional (Afifi et al, 2016 ; 2013 ; Alhalal et al, 2018 ; Anno et al, 2015 ; Badley et al, 2019 ; Baiden et al, 2021 ; Barron, 1997 ; Bendixen et al, 1994 ; Bottiroli et al, 2018 ; Brennenstuhl & Fuller-Thomson, 2015 ; Brown et al, 2018 ; Chartier et al, 2007 , 2010 ; Coles et al, 2015 ; Dennis et al, 2019 ; Díaz-Olavarrieta et al, 2002 ; England-Mason et al, 2018 ; Eriksen et al, 2016 ; Fowler et al, 2020 ; 2009 ; 2011 ; Hammond & Colman, 2020 ; Hanlon et al, 2020 ; Hart-Johnson & Green, 2012 ; Häuser et al, 2018 ; Jamieson & Steege, 1997 ; Jiao et al, 2015 ; Kamiya et al, 2016 ; Kascakova et al, 2020 ; Lee et al, 2009 ; Lin et al, 2021 ; Mays et al, 2021 ; McBeth et al, 2015 ; Nicol et al, 2016 ; Noteboom et al, 2021 ; Park et al, 2014a ; Pebole et al, 2022 ; Pierce et al, 2020 ; Reuchlein et al, 2016 ; Riedl et al, 2019 ; Sachs-Ericsson et al, 2007 ; 2017 ; Schrepf et al, 2018 ; Scott et al, 2011 ; Sheikh, 2018 , 2019 ; Shields et al, 2015 ; Sprang et al, 2020 ; Springer et al, 2007 ; Stickley et al, 2015 ; Talley et al, 1998 ; 1994 ; Tietjen et al, 2009 ; 2010 ...…”
Section: Resultsunclassified
“…Data were collected from a total of 826,452 participants (mean age of 44 years; range: 18–90 years), from community ( n = 48 studies) (Afifi et al, 2013 ; 2016 ; Alhalal et al, 2018 ; Badley et al, 2019 ; Baiden et al, 2021 ; Brennenstuhl & Fuller-Thomson, 2015 ; Brown et al, 2018 ; Chartier et al, 2007 , 2010 ; Coles et al, 2015 ; England-Mason et al, 2018 ; Eriksen et al, 2016 ; Fowler et al, 2020 ; Fuller-Thomson et al, 2009 ; 2011 ; Hammond & Colman, 2020 ; Hanlon et al, 2020 ; Kamiya et al, 2016 ; Kascakova et al, 2020 ; Kopec & Sayre, 2005 ; Lee et al, 2009 ; Lin et al, 2021 ; Noteboom et al, 2021 ; Park et al, 2014a ; Reuchlein et al, 2016 ; Sachs-Ericsson et al, 2007 ; 2017 ; Scott et al, 2011 ; Sheikh, 2018 , 2019 ; Shields et al, 2015 ; Stickley et al, 2015 ; Sumanen et al, 2007 ; Talley et al, 1994 ; 1998 ; Tietjen et al, 2015 ; 2017 ; Varinen et al, 2017 ; 2019 ; Wuest et al, 2008 ; 2009 ; 2010 ; Xu et al, 2013 ), clinical care ( n = 19) (As-Sanie et al, 2014 ; Barron, 1997 ; Chandan et al, 2020 ; Dennis et al, 2019 ; Díaz-Olavarrieta et al, 2002 ; Hart-Johnson & Green, 2012 ; Jamieson & Steege, 1997 ; Jiao et al, 2015 ; Ju et al, 2020 ; Mays et al, 2021 ; Nicol et al, 2016 ; Pebole et al,…”
Section: Resultsunclassified
See 2 more Smart Citations
“…As one of the major types of adverse childhood experiences, sexual abuse during childhood has been suggested to be associated with multiple adverse health risk behaviors and outcomes such as risky sexual behaviors (8), teenage pregnancy (9), and problems connected with intimacy relationships (10), to name a few. A previous study has indicated that sexual trauma may disrupt the psychosocial development of abused children, operate through cognitive and emotional processes, and further manifest in behaviors (11,12). Some amount of research seems to suggest that early sexual debut plays a mediating role in the association between childhood sexual abuse (CSA) and risky sexual behaviors in later life (13).…”
Section: Introductionmentioning
confidence: 99%